Modelling and analysis of a delayed viral infection model with follicular dendritic cell - Yan Geng; Jinhu Xu (Electronic Research Archive)
In this paper, we propose a new viral infection model by incorporating a new compartment for follicular dendritic cell (FDC), nonlinear incidence, CTL immune response, and two intracellular delays. The main purpose of the paper is to make an improvement and supplement to the global dynamics of the model proposed by Callaway and Perelson (2002), in which global stability has not been studied. The global stabilities of equilibria are established by constructing corresponding Lyapunov functionals in terms of two threshold parameters, $ \mathfrak{R}_0 $ and $ \mathfrak{R}_1 $. The obtained results imply that both nonlinear incidence and intracellular time delays have no impact on the stability of the model.